Ventilator-Associated Pneumonia in Neonates Admitted to a Tertiary Care NICU in Bulgaria - Rangelova, Vanya R.; Raycheva, Ralitsa D.; Kevorkyan, Ani K.; Krasteva, Maya B.; Kalchev, Yordan I. (Frontiers in Pediatrics, 2022)
Ventilator-associated pneumonia (VAP) is the second most common hospital-acquired infection (HAI) among neonatal patients in the intensive care units (ICUs) and is a serious challenge for neonatologists because it affects critically ill patients who need prolonged mechanical ventilation. In Bulgaria, there is no detailed data at regional and national levels on the characteristics of VAP in newborns, which imposes a necessity for specific studies of risk factors and aetiology of VAP. The aim of the study was to analyze the frequency, characteristics and risk factors for the occurrence of VAP in newborns hospitalized in intensive care unit. This was a prospective study, conducted between January 2017 and June 2018 in the NICU of University Hospital “St. George” Plovdiv, Bulgaria. The sample consisted of 507 neonates, followed up prospectively, 107 of whom were placed on mechanical ventilation for ≥ 48 hours. VAP was diagnosed in 33 out of 107 neonates (31%). The VAP incidence rate was 35.06/1.000 ventilator days. We confirmed differences between the median birth weight (U=924, p=0.045) and average gestational age (t=2.14, p=0.04) of the patients with and without VAP. The average stay of patients with VAP in the NICU was statistically significantly longer than the hospital stay of non-VAP patients (35.70±21.84 days vs 21.77±17.27 days (t=3.241, p=0.002). In neonates with VAP, the duration of mechanical ventilation was statistically significantly longer compared with non-VAP patients (16.88±11.99 vs 5.42±4.48; t=5.249, р=0.000). A statistically significant prevalence of Gram-negative bacteria among VAP patients was demonstrated (91%) compared to the Gram-positive (9%), p<0.05. The leading causative agent of VAP was Klebsiella pneumoniaе ESBLs + (27%), followed by Acinetobacter baumannii (14%), Pseudomonas aeruginosa (12%), and Escherichia coli (12%). In multivariate logistic regression, mechanical ventilation>7 days was established as an independent risk factor for VAP (OR 3.6; 95% CI: 1.7-6.5, p=0.003). VAP remains a serious and outstanding issue in pediatric and neonatal intensive care units. The findings of the current study emphasize that the birth weight, gestational age, and duration of hospital stay have a significant association with ventilator-associated pneumonia.